2017
DOI: 10.1039/c7tc03429f
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photoluminescence evolution of nanodots during pyrolysis of citric acid: from molecular nanoclusters to carbogenic nanoparticles

Abstract: Dynamic rheological measurements indicate that supra-molecules, polymers and carbogenic nanoparticles are generated successively during pyrolysis of citric acid based nanodots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 57 publications
3
69
1
Order By: Relevance
“…The partial conversion from low molecular weight fluorophore to the π-conjugated carbon core with increasing temperature suggested that the unconverted fluorophore may bind to the larger π-conjugated domains to give rise to so-called quasi CNDs (CNDs coated with molecular fluorophores). This observation was supported by a few other recently studied CNDs systems 68 .…”
Section: Fallacies and Artifacts In Carbogenic Nanodotssupporting
confidence: 75%
“…The partial conversion from low molecular weight fluorophore to the π-conjugated carbon core with increasing temperature suggested that the unconverted fluorophore may bind to the larger π-conjugated domains to give rise to so-called quasi CNDs (CNDs coated with molecular fluorophores). This observation was supported by a few other recently studied CNDs systems 68 .…”
Section: Fallacies and Artifacts In Carbogenic Nanodotssupporting
confidence: 75%
“…Indeed, it has been established that some bottom-up syntheses of CDs can produce small fluorescent molecular derivatives, formed alongside with the carbonization process, both if the synthesis is carried out in water [183] or in an organic solvent [15]. In particular, the production of CDs from the decomposition of citric acid and a N-containing precursor lead to the formation of 2-pyridone derivatives [91,182], such as citrazinic acid [102,183,184], and the relative yield of the molecular byproducts and CD cores changes in favour of the latter at higher synthesis temperatures [161,186,187].…”
Section: Emission Mechanismsmentioning
confidence: 99%
“…Single-particle studies [101] have demonstrated that different resolved spectral forms can be attributed to individual particles, suggesting the possibility of integrating different types of electronic transitions within the nanoscale composition. Transition from one emissive form to another may also proceed in the course of synthesis and as a function of reaction temperature and, thus, it can be thought that carbon particles initially form an association of molecular fluorophores and then they attain the carbonic core with a dramatic change of the emission [88,91,163]. All this suggests that thermodynamic and kinetic drivers exist for ordering, resulting in quite discrete supramolecular forms possessing discrete electronic states.…”
Section: What Determines the Excitation And Emission Peak Positions?mentioning
confidence: 99%